Detecção e caracterização de calicivírus em amostras fecais de crianças frequentadoras de creche em Goiânia, Goiás - Oliveira, Denisy Marques Mendanha de (2013)
The calicivirus (CV) are important etiologic agents of acute gastroenteritis, affecting people of different ages and in various parts of the world. The present study aimed at the detection and molecular characterization of caliciviruses - norovirus (NoV) and sapovirus (SaV) - from fecal samples from children attending a daycare in Goiânia, Goiás. Were collected and analyzed 539 fecal samples 56 children from October 2009 to October 2011. The viral detection and genotyping was done by polymerase chain reaction post-transcription (RT-PCR) and by genomic sequencing using primers designed for partial regions of the viral capsid. From the 56 children participants of the study, 29 (51.8%) had at least one positive sample for CV during the study period. Positive children, 21 (37.5%) had at least one sample for NoV, 16 (28.6%) for SaV and eight (14.3%) positivity to both the virus. The CV were detected in children of both genders, and a higher positivity rate was detected among children aged 13 to 24 months, when compared to the other age groups. A significantly higher positivity for CV was observed in samples from asymptomatic children, and a defined seasonality pattern was not detected for these agents. In terms of molecular characterization for NoV the circulation of samples GII.6, GII.2, GII.1, GII.4, GI.1 and GI.7 was observed, whereas for SaV samples were detected GI.1 and GI.3. During the study period five outbreaks took place, being three of NoV, GII.6, GII.2 and GII.1, two SaV GI.1 and GI.3. Two children presented by prolonged NoV excretion, one for two months and another for 23 days. Twelve (20.4%) children had more than infection for NoV and / or SaV. This study showed circulation of CV at the daycare, a higher rate of infection in asymptomatic children, and prolonged de NoV excretion, which may have contributed to the occurrence of outbreaks and to the dissemination of these agents in such environment.